2020
DOI: 10.1016/j.aquatox.2020.105519
|View full text |Cite
|
Sign up to set email alerts
|

Negative impacts of the sea lice prophylactic emamectin benzoate on the survival of hatchery released salmon smolts in rivers

Abstract: Emamectin benzoate (EB) is a prophylactic pharmaceutical used to protect Atlantic salmon (Salmo salar) smolts migrating out of rivers and into the ocean against sea lice parasites.Randomized control trials comparing the marine survival of smolts treated with EB to a control group is used to calculate the fraction of marine mortality attributable to sea lice parasitism. However, it is assumed that there is no baseline difference in survival induced by the application of EB treatment. We used a combined laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Despite this new designation, owing to the industrial production of fish being farmed in open sea cages, sea lice are not an isolated stressor. Atlantic salmon in Norway are facing urgent threats from multiple angles [9,21]. Multiple stressors in ecological systems are challenging to unravel because interactions can be synergistic, confounding management efforts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this new designation, owing to the industrial production of fish being farmed in open sea cages, sea lice are not an isolated stressor. Atlantic salmon in Norway are facing urgent threats from multiple angles [9,21]. Multiple stressors in ecological systems are challenging to unravel because interactions can be synergistic, confounding management efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Evidently, the anti-lice treatment only partially shielded the out-migrating salmon from sea lice during periods of high infestation pressure. This is in line with other recent studies suggesting that (i) salmon lice in western Norway are resistant to emamectin benzoate [31], (ii) the effect of treatment in RCTs is only significant and positive when infestation pressure is high [19], (iii) treatment may not be effective across all individuals in the group [20], and (iv) treatment may also incur negative effects on marine survival cancelling out the positive effect of the antiparasitic treatment on the return rate of salmon [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jackson et al, 2013;Skilbrei et al, 2013;Vollset et al, 2016). However, recent studies indicate potential methodological biases (Lennox et al, 2020;Vollset et al, 2023), raising concerns about the accuracy of previous findings and the validity of subsequent conclusions. Obtaining quantitative estimates of overall stock abundance typically demands year-round trapping facilities, which are limited (Thorstad et al, 2014).…”
Section: Negative Association Of Sea Lice From Fish Farms On Wild Sal...mentioning
confidence: 99%
“…Other researchers have disputed this conclusion and find, using similar data, that the density of farm lice substantially affects wild salmon returns (Gargan et al, 2012;Krkošek et al, 2013;Otero et al, 2011;Shephard & Gargan, 2017. Moreover, recent studies suggest that the impact of sea lice may have been underestimated in RCTs, as indicated by the reduction in the survival of salmon smolt associated with the treatment (Lennox et al, 2020), and by findings of reduced treatment efficacy attributed to increased resistance among sea lice (Vollset et al, 2023).…”
Section: Introductionmentioning
confidence: 99%